Penerapan E-Government melalui Aplikasi Sistem Informasi Keluarga (SIGA) di BKKBN Provinsi Gorontalo - Zhafirah Nuralifya Rilani Kasim; Yanti Aneta; Sri Yulianty Mozin (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
This study aims to analyze the availability of data centers and regional promotion needs in supporting e-government implementation through the Family Information System Application (SIGA) at BKKBN Gorontalo Province. It also assesses how SIGA and its integrated dialog features contribute to public services. The findings indicate that data input in SIGA has reached 100%, covering family planning services, field supervision, and families at risk of stunting, both in monthly and annual reports. However, this completeness does not fully reflect field realities, particularly regarding youth groups outside formal education who remain underdocumented. Despite this, SIGA data has become a reference for regional health information policy development. Overall, SIGA has improved public service efficiency through fast, accurate, and timely data delivery. Yet, the system remains limited in providing interactive, two-way communication between government and citizens. This study recommends enhancing SIGA’s dialog function and engaging underrepresented community groups to support inclusive and responsive public services.